Assessment on the Stable and High-Capacity Na-Se Batteries with Carbonate Electrolytes - Erdol, Zeynep; Ata, Ali; Demir-Cakan, Rezan (Wiley-V C H Verlag Gmbh, 2022)
Factors affecting proper functioning of Na-Se system are investigated focusing on the polyselenide formation in ether- and carbonate-based electrolytes. To do so, Se cathode is prepared by ball milling with commercial carbon and selenium powders. It is revealed that the soluble polyselenide species form in ether while no signature in carbonates proven by the in-situ cyclic voltammetry and ex-situ ultraviolet-visible spectroscopy measurements as well as monitoring self-discharge behaviours. Different Se discharge mechanism is also highlighted by staircase potentio electrochemical impedance spectroscopy (SPEIS) that is an impedance measurement applied to each potential step. Volume expansion is targeted using different types of binders in which carboxyl methylcellulose-styrene butadiene rubber (CMC-SBR) delivers the highest reversible capacity and the best rate performance resulting from its high adhesion strength. To further improve the performances, fluoroethylene carbonate (FEC) is used as a film forming additive that preserves Na metal integrity proven by the Na-Na symmetric cells and voltage relaxation upon cycling. As a whole, binders and electrolyte compositions are found to be the two crucial factors to obtain stable and high-capacity Na-Se cells. This study underlines that much effort needs to be put on the strategies to overcome volume expansion than that of Se confinement into porous cathode.
Keywords: binder; carbonate electrolytes; ether electrolytes; Na-Se batteries; volume expansion